Evaluating the Lexical Load of the Reading Comprehension Texts in EFL Textbooks - El Motabit, Abdelmalek (International Journal of Linguistics and Translation Studies, 2020)
Research has revealed numerous problems regarding the teaching and learning of EFL in Morocco. One of these problems concerns students’ performance in reading comprehension tasks. Given the assumption that a large proportion of the problem can be attributed to lexical deficiency, this study sets out to evaluate the vocabulary load of the reading comprehension texts in EFL second-year baccalaureate textbooks. This was actualized through determining how much text coverage students could achieve with their vocabulary knowledge. To this end, a sample of 106 Moroccan bac2 (second-year baccalaureate) students was non-randomly sampled, and their vocabulary knowledge was assessed using an updated version of the Vocabulary Levels Test (VLT). In parallel, the vocabulary profiles of the reading texts in the three EFL textbooks were described using the Vocabulary Profiler software. Results have shown that students have a rather impoverished vocabulary knowledge of approximately 1317 word families, which have thus revealed a gap between their actual knowledge and the lexical load contained in their textbooks.